A handbook on special senses (vision, hearing, smell and taste) - Aung, Nilar; Razali , Ailin; Cho, Maung Maung (2013)

(untitled)
The basic sciences have played an essential role in the training of doctors. Physiology provides the scientific foundation for the field of medicine and all other professions related to human health and physical performance. Vision, hearing, smell and taste considered a special senses and each of these special senses works in concert with the nervous system to assist the body in coping with the environment changes experienced through the day. The scope of special senses have been widen and hence become more complicated for medical students. Text books and references are plentiful; however students might find it difficult to remember the facts due to the expanding knowledge in this particular area. The impetus of writing this book is to set out to provide comprehensive knowledge of the special senses, laid out in a very simplistic manner and designed in a learner friendly format. Therefore, without opening the heavy books, a learner can effectively use this handbook to know the important of special senses and their clinical correlations. This book will benefit not only the medical students but also students pursuing studies in other health-related fields such as dentistry, nursing and allied health.